2023
DOI: 10.1021/acs.cgd.2c01309
|View full text |Cite
|
Sign up to set email alerts
|

Gelation Mechanism and Oscillatory Temperature Control Strategy in Perindopril Erbumine Solution Crystallization

Abstract: The gelation phenomenon often occurs in the solution crystallization process, which would seriously affect the process robustness and product quality. In this paper, the gelation phenomenon during the solution crystallization of perindopril erbumine (PDP) was systematically studied by spectroscopy and microscopy techniques. The results suggest that the PDP gel does not have the characteristic diffraction peak of the PDP crystal and the infrared spectrum has changed significantly compared with that of the cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although much research has been focused on the formation of gel, the formation mechanism is still not fully understood, making it difficult to identify the key factors of gelation and regulate the gelation process effectively. Besides, several methods have been proposed to avoid the gelation phenomenon in the crystallization process, including the reverse antisolvent crystallization (RAC) method, oscillating temperature control strategy, seeding-assisted crystallization etc. However, high-quality seeds are generally needed in the seed-assisted method, which limits its application.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although much research has been focused on the formation of gel, the formation mechanism is still not fully understood, making it difficult to identify the key factors of gelation and regulate the gelation process effectively. Besides, several methods have been proposed to avoid the gelation phenomenon in the crystallization process, including the reverse antisolvent crystallization (RAC) method, oscillating temperature control strategy, seeding-assisted crystallization etc. However, high-quality seeds are generally needed in the seed-assisted method, which limits its application.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the crystal products obtained through gel-mediated crystallization typically have smaller particle sizes and are prone to aggregation, resulting in higher residual impurities. 19 Therefore, gelation should be regulated precisely in the production of drugs. It is found that the gelation phenomenon often occurs in the crystallization process of tilmicosin phosphate, which leads to small particle sizes and easy aggregation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation